A speculation on the tandem fasciclin 1 repeat of FLA4 proteins in angiosperms. (2nd September 2018) - Turupcu, Aysegül; Almohamed, Wisam; Oostenbrink, Chris; Seifert, Georg J.
ABSTRACT: The Arabidopsis thaliana Fasciclin like arabinogalactan protein 4 (FLA4) locus is required for normal root growth in a linear genetic pathway with the FEI1 and FEI2 loci coding for receptor-like kinases. The two Fas1 domains of FLA4 are conserved among angiosperms but only the C-terminal Fas1 domain is required for genetic function. We show that at low salt deletion of the N-terminal Fas1 domain of transgenic FLA4 leads to enhanced root elongation compared to the tandem Fas1 wild type version. Modeling the hypothetical interaction between FLA4 and FEI1 we show that the predicted interaction is predominantly involving the C-terminal Fas1 domain. Relative conformational mobility between the two FLA4 Fas1 domains might regulate the interaction with the FEI receptor kinases. We therefore speculate that the FLA4 FEI complex might be a sensor for environmental conditions in the apoplast.